2017
DOI: 10.15761/bem.1000133
|View full text |Cite
|
Sign up to set email alerts
|

eMouveRecherche: the first scientific application to promote light-intensity activity for the prevention of chronic diseases

Abstract: Physical inactivity and long sedentary time are involved in the development of chronic diseases. The aim of this study was to compare the intensity of spontaneous physical activity in two population samples consisting of 30 normal weight and 30 overweight or obese adults. Physical activity on an ordinary day was evaluated using the eMouveRecherche application that collected and sent smartphone accelerometry data to the ActivCollector Web platform via Internet. The algorithms implemented on the platform can acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Thus, this two-month lockdown did not lead to a sustainable low level of PA. In one of our previous works published in 2018, we showed that normal-weight adults (mean age 33 ± 9 years) in free-living conditions spent 65.2%, 29.4%, 4.9% and 0.4% in immobility, light-, moderate and vigorous- intensity activities, respectively ( Rousset et al, 2018 ). Compared to this activity split, that of the students post lockdown seems a little different for immobile and light intensity activity.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, this two-month lockdown did not lead to a sustainable low level of PA. In one of our previous works published in 2018, we showed that normal-weight adults (mean age 33 ± 9 years) in free-living conditions spent 65.2%, 29.4%, 4.9% and 0.4% in immobility, light-, moderate and vigorous- intensity activities, respectively ( Rousset et al, 2018 ). Compared to this activity split, that of the students post lockdown seems a little different for immobile and light intensity activity.…”
Section: Discussionmentioning
confidence: 87%
“…In free-living conditions, Overweight (OW) individuals spent more time immobile (81% vs. 65% of the waking period) and twice less time in light-intensity activities than Normal-Weight (NW) individuals (15% vs. 29%). No difference in moderate or vigorous intensity activity was observed between the two groups [17]. Such gaps in time spent in immobile or light-intensity activities constitute a behavioral marker of BMI or fat mass.…”
Section: Introductionmentioning
confidence: 73%
“…Obese people are more sedentary than NW individuals [17,[19][20][21]. Belletiere, et al showed that often interrupting sitting posture was associated with lower BMI and waist circumference in an Australian adult cohort (AusDiab) [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations